Medieval Franciscan approaches to the Virgin Mary
1 online resource.
Keywords: This volume offers a sample of the many ways that medieval Franciscans wrote, represented in art, and preached about the ‘model of models’ of the medieval religious experience, the Virgin Mary. This is an extremely valuable collection of essays that highlight the significant role the Franciscans played in developing Mariology in the Middle Ages. Beginning with Francis, Clare, and Anthony, a number of significant theologians, spiritual writers, preachers, and artists are presented in their attempt to capture the significance and meaning of the Virgin Mary in the context of the late Middle Ages within the Franciscan movement. Contributors are Luciano Bertazzo, Michael W. Blastic, Rachel Fulton Brown, Leah Marie Buturain, Marzia Ceschia, Holly Flora, Alessia Francone, J. Isaac Goff, Darrelyn Gunzburg, Mary Beth Ingham, Christiaan Kappes, Steven J. McMichael, Pacelli Millane, Kimberly Rivers, Filippo Sedda, and Christopher J. Shorrock.